Pendirian Usaha Spa di Sadara Resort sebagai Upaya Optimalisasi Pendapatan Hotel - Sulistiyaningsih; Astawa, I Putu; Sutama, Ketut (JURNAL BISNIS HOSPITALITI, 2025)
This thesis project aims to determine the most suitable model for spa development within a hospitality context. It also discusses the implementation process required to establish the spa effectively according to the chosen model. Furthermore, the thesis project analyses whether the direct establishment and management of the spa by Sadara Resort can contribute to increasing the hotel's overall revenue, thereby supporting its long-term financial sustainability and service quality improvement. This thesis project adopts the Planning, Organizing, Actuating, and Controlling (POAC) framework. It uses qualitative data, including primary data from interviews with Sadara Resort’s management and secondary data from guest reviews on facilities and services. The data analysis technique is qualitative analysis, consisting of data collection, data reduction, data display, and conclusion drawing. The establishment of a spa at Sadara Resort aligns with the implementation of the POAC (Planning, Organizing, Actuating, and Controlling) model. Through careful planning and independent management, the spa business has effectively increased revenue and made a significant contribution to the hotel’s overall income. This demonstrates the financial advantages of integrating wellness services into the resort’s core operations. Independently managing a business, rather than outsourcing it to third parties, can lead to higher revenue generation by retaining full control over operations and profits. This approach requires the ability to identify current market trends, opportunities, and customer needs. Understanding these elements is essential for detecting business gaps. Once identified, a comprehensive analysis must assess their financial and operational impact. If results are favorable, business enhancement or development plans should be prepared accordingly.